Réponses

2014-01-12T23:34:32+01:00
Bonsoir

(7 au carré 3 - 3au carré 3 x 2) au carré 2

(7^3-3^3\times2)^2=(343-27\times2)^2=(343-54)^2=289^2=83521

- 2sur3 x (5sur2)au carré 2 - 3 x (-2sur3) au carré 3

\dfrac{-2}{3}\times(\dfrac{5}{2})^2-3\times(\dfrac{-2}{3})^3=\dfrac{-2}{3}\times\dfrac{25}{4}-3\times(\dfrac{-8}{27})\\\\=\dfrac{-1}{3}\times\dfrac{25}{2}-(\dfrac{-8}{9})=\dfrac{-25}{6}+\dfrac{8}{9}=\dfrac{-25\times3}{6\times3}+\dfrac{8\times2}{9\times2}\\\\=\dfrac{-75}{18}+\dfrac{16}{18}=\dfrac{-59}{18}